2016
DOI: 10.13080/z-a.2016.103.035
|View full text |Cite
|
Sign up to set email alerts
|

Grain chemical composition of different varieties of winter cereals

Abstract: The objective of this research was to evaluate the chemical composition of grain of 20 winter wheat, rye and triticale varieties grown in Lithuania. The grain of the tested varieties was analysed for crude protein, crude fat, crude ash, crude fibre, and amino acids. The Pearson's correlation coefficient between the components of grain chemical composition (except amino acids) was calculated. The highest concentration of crude protein was determined for the variety 'SW Talentro' (triticale) and the lowest for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 18 publications
6
24
1
Order By: Relevance
“…The 1000 kernel weight ranged from 39.7 g ('Kaupo') to 44.6 g ('Su Drive') on average ( Table 2). Similar results were obtained in Lithuania (Alijošius et al, 2016) where in seven rye varieties average of 1000 grains weight were 43.9 g. In our investigation, the 1000 kernel weight was highly influenced by cultivar (69%) and cultivar × year (19%), while influence of harvest year was smaller (10%), however in Hansen and colleagues (2016) experiments 1000 kernel weight dependency on year complete to 65% but the influence of cultivar -25%, whole cultivar × year -5% (Tab. 3).…”
Section: Grain Characteristicssupporting
confidence: 90%
“…The 1000 kernel weight ranged from 39.7 g ('Kaupo') to 44.6 g ('Su Drive') on average ( Table 2). Similar results were obtained in Lithuania (Alijošius et al, 2016) where in seven rye varieties average of 1000 grains weight were 43.9 g. In our investigation, the 1000 kernel weight was highly influenced by cultivar (69%) and cultivar × year (19%), while influence of harvest year was smaller (10%), however in Hansen and colleagues (2016) experiments 1000 kernel weight dependency on year complete to 65% but the influence of cultivar -25%, whole cultivar × year -5% (Tab. 3).…”
Section: Grain Characteristicssupporting
confidence: 90%
“…Localised fertilisation results in a greater concentration of nutrients in the neighbourhood of plants and their better nutrition [43]. A variable environment and the agronomic treatments did not have a significant effect on the ash content in flour, although Alijošius et al [44] point to a high variation in that trait. e authors cited, however, investigated the grain of six wheat cultivars, and not one cultivar, which can point to a high genetic variation and not environment-agronomic variation of that trait.…”
Section: Resultsmentioning
confidence: 93%
“…In turn, Fernandez-Figares et al (2000) showed varietal differences in the concentration of amino acids in triticale only for two amino acids: Lys and Met. Alijošius et al (2016), in their studies involving 7 winter triticale genotypes showed variation in the concentration of all 16 amino acids tested, with the difference being the highest for Met, followed by Phe, Glu and Pro.…”
Section: Resultsmentioning
confidence: 93%
“…Triticale grains are mainly used as valuable feed for animals, but they are becoming more and more popular as consumer grain (Coffey & Gerrits, 2009). Triticale has a high nutritional value due to its high content of protein in grains and a better amino acid composition than wheat (Alijošius et al, 2016). The quality of cereal grain is shaped by the complex activity of habitat, agronomic and genetic factors (Djekić et al, 2014;Järvan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%